FtsH2-Dependent Proteolysis of EXECUTER1 Is Essential in Mediating Singlet Oxygen-Triggered Retrograde Signaling in Arabidopsis thaliana - Dogra, Vivek; Duan, Jianli; Lee, Keun Pyo; Lv, Shanshan; Liu, Renyi; Kim, Chanhong (Frontiers in Plant Science, 2017)
Photosystem II reaction center (PSII RC) and light-harvesting complex (LHC) inevitably generate highly reactive singlet oxygen (1O2) that can impose photo-oxidative damage, especially when the rate of generation exceeds the rate of detoxification. Besides being toxic, 1O2 has also been ascribed to trigger retrograde signaling, which leads to nuclear gene expression changes. Two distinctive molecular components appear to regulate 1O2 signaling: a volatile signaling molecule ß-cyclocitral (ß-CC) generated upon oxidation of ß-carotene by 1O2 in PSII RC assembled in grana core, and a thylakoid membrane-bound FtsH2 metalloprotease that promotes 1O2-triggered signaling through the proteolysis of EXECUTER1 (EX1) proteins associated with PSII in grana margin. The role of FtsH2 protease in 1O2 signaling was established recently in the conditional fluorescent (flu) mutant of Arabidopsis thaliana that generates 1O2 upon dark-to-light shift. The flu mutant lacking functional FtsH2 significantly impairs 1O2-triggered and EX1-mediated cell death. In the present study, the role of FtsH2 in the induction of 1O2 signaling was further clarified by analyzing the FtsH2-dependent nuclear gene expression changes in the flu mutant. Genome-wide transcriptome analysis showed that the inactivation of FtsH2 repressed the majority (85%) of the EX1-dependent 1O2-responsive genes (ESORGs), providing direct connection between FtsH2-mediated EX1 degradation and 1O2-triggered gene expression changes. Furthermore, the overlap between β-CC-induced genes and EX1-FtsH2-dependent genes was very limited, further supporting the coexistence of two distinctive 1O2 signaling pathways.